Postharvest application of calcium, packaging material and hot water treatment on quality of mango (Mangifera indica L.) cv. Zardalu - Shahin, Nadira; Kumar, Rajesh; Karuna, K; Mankar, Abhay (Journal of Postharvest Technology, 2020)
Development of methods for delaying ripening and senescence of mango without adverse effect on quality is of immense value in prolonging  shelf life and increasing the marketing potential. The Zardalu mango fruits were subjected to different chemicals and their effect of fruit quality during storage was assessed. The minimum PLW (9.93%) was recorded in fruits packed under perforated polyethylene bag + CaCl2 2% (T6).  The highest PLW (15.19%) was obtained in fruits stored under control (T8). However, minimum ripening (42.29%) was observed in fruits treated  with CaCl2 2% and packed in perforated polyethylene bag (T6) while the highest ripening (56.67%) was noted under control (T8). The minimum  spoilage loss (8.60%) was obtained with perforated polyethylene bag + CaCl2 2 % (T6) which proved its superiority over remaining treatments.  However, the next effective treatment was perforated polyethylene bag + CaCl2 1 % (T5) in reducing spoilage loss of fruits. The maximum  spoilage loss (14.81%) was recorded under control (T8). It is obvious from the data that the fruits stored under perforated polyethylene bag +  CaCl2 2% (T6), scored maximum marks and rated as good grade followed by perforated polyethylene bag + CaCl2 1% (T5), while poor grade  was obtained under control.
Keywords: Mango; CaCl2; packaging materials,; hot water treatment; , postharvest; spoilage